Music Creativity in Musical Drama Learning Through The Cooperative Model of Think-Pair-Share - Heldisari, Hana Permata (Universitas Negeri Medan, 2024)
The need for creativity in music refers to an idea of novelty such as a new work, a new method, or a new technique. Especially music in an integrated performing art, musical drama for example. Communication between the director and music director is one part of interpersonal intelligence which must be able to understand each other and benefit both parties. Therefore, it is necessary to conduct research to find out how musical creativity develops through think-pair-share type cooperative models This study uses a qualitative approach with a descriptive type using the Miles and Huberman analysis model, namely data collection, data reduction, data presentation, and conclusions. The object in this study is interpersonal intelligence and musical creativity. The subject of this study was determined by purpossive sampling technique with criteria for participating in musical drama courses in 2023 consisting of 12 people. Data collection is carried out using techniques in depth interviews, participant observation, and documentation of works so that they will be validated using triangulation techniques. The results of this study explain that musical creativity will emerge in line with the situation needed in drama, including collaboration between modern music with tambourine and gambus, modern music with gamelan and ethnic flute. In addition, this think-pair-share type cooperative model allows students to better understand each other and process music in accordance with existing human resources.